Post–below-knee amputation venous thromboembolism and mortality in United States veterans - Khanh P. Nguyen; Joshua B. Gruber; Megan L. Mertzel; Cecelia Madison; Reid Thompson; Kenneth Gundle; Scott Damrauer; Kristen M. Sanfilippo (Research and Practice in Thrombosis and Haemostasis)
Background: Patients who undergo below-knee surgical amputation (BKA) are at risk of postoperative venous thromboembolism (VTE). Limited prior studies quantified the rate of VTE post-BKA or the association of VTE with survival in this population. Objectives: We aimed to assess the incidence of post-BKA VTE and the association with all-cause mortality in a cohort of United States veterans. Methods: This was a retrospective cohort study of veterans who underwent surgical BKA between October 2016 and January 2023. We identified VTE within 90 days post-BKA using a previously validated algorithm combining International Classification of Diseases codes with a new anticoagulant prescription, placement of an inferior vena cava filter, or death within 30 days. A time-dependent Cox proportional hazard model tested the association between VTE and death while adjusting for potential confounders. A sensitivity analysis removed individuals categorized as having an acute VTE based on the International Classification of Diseases for VTE plus death within 30 days. Results: A total of 6305 patients underwent a first-time surgical BKA. Of these, 132 experienced a VTE within 90 days post-BKA. Younger age was associated with a reduced risk of post-BKA VTE. After adjusting for confounders, VTE within 90 days of BKA was associated with a 3-fold increase in mortality (adjusted hazard ratio, 3.17, 95% CI, 2.12-4.17). Conclusion: Patients who had a VTE within 90 days of BKA had a higher mortality than those without VTE post-BKA. Future studies are warranted to confirm these findings and investigate strategies to prevent post-BKA VTE.